2021
DOI: 10.1088/1612-202x/ac14c5
|View full text |Cite
|
Sign up to set email alerts
|

Elastic electron-proton scattering in the presence of a circularly polarized laser field

Abstract: Owing to recent advances in laser technology, it has become important to investigate fundamental laser-assisted processes in very powerful laser fields. In the present work and within the framework of laser-assisted quantum electrodynamics, electron-proton scattering was considered in the presence of a strong electromagnetic field of circular polarization. First, we present a study of the process where we only take into account the relativistic dressing of the electron without the proton. Then, in order to exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This would support and justify the choice made previously by some authors [35,36] to study the same scattering process without taking into account the laser-dressing of muon at the field strength of 5.18 × 10 7 V cm −1 . Recently, Dahiri et al [20] considered the effect of proton dressing in the laser assisted electron-proton scattering and found that it begins to appear at laser field strengths greater than or equal to 10 10 V cm −1 due to the heavy mass of the proton. From table 1, it is also clear to us that the laser-dressing of muon has rendered the DCS lower than before.…”
Section: Muon-dressing Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…This would support and justify the choice made previously by some authors [35,36] to study the same scattering process without taking into account the laser-dressing of muon at the field strength of 5.18 × 10 7 V cm −1 . Recently, Dahiri et al [20] considered the effect of proton dressing in the laser assisted electron-proton scattering and found that it begins to appear at laser field strengths greater than or equal to 10 10 V cm −1 due to the heavy mass of the proton. From table 1, it is also clear to us that the laser-dressing of muon has rendered the DCS lower than before.…”
Section: Muon-dressing Effectmentioning
confidence: 99%
“…Electron-positron scattering in the field of a light wave was studied in the works [18,19]. Elastic electron-proton scattering in the presence of a circularly [20] or linearly [21,22] polarized laser field has been also reported. In addition to QED processes, many authors have studied some processes of the electroweak theory such as the decay of particles [23,24] and the Higgs-boson production [25] in the presence of a circularly polarized laser field.…”
Section: Introductionmentioning
confidence: 99%
“…Chirality describes an object that cannot be superimposed on its mirror image, which is an important feature of symmetry inherent in the natural world. Chiral light fields are generally considered an optical access to the helicity of a quantum system and have been applied in various fields, varying from the examination of bodily tissues, chemical synthesis, and magneto-optical memory to microfabrication and quantum electrodynamics research. , In the light–matter interaction context, the circular polarization of light fields is directly associated with the spin of electrons, which enables an optical method to orientate and align the spin of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to atomic physics processes, various authors studied laser-assisted scattering processes in quantum field theory (QED). The relativistic elastic scattering of an electron by a proton has been analyzed in the presence of a linearly and circularly polarized laser field in [16,17,18]. In addition, in Refs [19,20,21], the authors have studied new phenomena of scattering of an electron by a muon in the laser field with different polarizations.…”
Section: Introductionmentioning
confidence: 99%